Clinical–radiological–pathological correlation in chronic thromboembolic pulmonary hypertension - Tom Verbelen; Laurent Godinas; Peter Dorfmüller; Deepa Gopalan; Robin Condliffe; Marion Delcroix (European Respiratory Review, 2023)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare and potentially life-threatening complication of acute pulmonary embolism. It is characterised by persistent fibro-thrombotic pulmonary vascular obstructions and elevated pulmonary artery pressure leading to right heart failure. The diagnosis is based on two steps, as follows: 1) suspicion based on symptoms, echocardiography and ventilation/perfusion scan and 2) confirmation with right heart catheterisation, computed tomography pulmonary angiography and, in most cases, digital subtraction angiography. The management of CTEPH requires a multimodal approach, involving medical therapy, interventional procedures and surgical intervention. This clinical–radiological–pathological correlation paper illustrates the diagnostic and therapeutic management of two patients. The first had chronic thromboembolic pulmonary disease without pulmonary hypertension at rest but with significant physical limitation and was successfully treated with pulmonary endarterectomy. The second patient had CTEPH associated with splenectomy and was considered unsuitable for surgery because of exclusive subsegmental lesions combined with severe pulmonary hypertension. The patient benefited from multimodal treatment involving medical therapy followed by multiple sessions of balloon pulmonary angioplasty. Both patients had normalised functional capacity and pulmonary haemodynamics 3–6 months after the interventional treatment. These two examples show that chronic thromboembolic pulmonary diseases are curable if diagnosed promptly and referred to CTEPH centres for specialist treatment.